A comparison study of stock market returns given by the Newsweek 500 Green Companies and broad market indices in US - Sanjeevkumar, Virmala (Macrothink Institute, 2011)
"Going green" is no longer a fringe topic.The green revolution has already started, and is going green from the bottom up and the top down.Going green is about sustainability. Corporations exhaust resources, pollute the environment, generate large amount of waste and engage themselves in tons of unsustainable practices. These practices become an expense to the nation.Businesses are finding ways to protect the environment, particularly though developing standards and green certification programs. Some corporations are responding to the requirements of consumers to buy products with less impact on the environment (i.e) in their creation, packaging, marketing, use, and disposal.Furthermore with scientific and global consensus that human activities and carbon emissions contribute significantly to climate change, corporations no longer have the choice to ignore being environmentally sensitive. Green practices can be rewarding in the long run as it ensures that natural resources can be sustained as long as possible. Many investors are also prepared to put their money into green businesses because they see that sustainable practices are actually more profitable in the long term.Recent developments in technology have made it easier to protect the environment, and many businesses have learned that a sustainable supply chain is a valuable asset.